2015
DOI: 10.1016/j.smallrumres.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Browsing ratio, species intake, and milk fatty acid composition of goats foraging on alpine open grassland and grazable forestland

Abstract: Aims of this study were to investigate diet selection of dairy goats foraging on two alpine vegetation types and to assess the related effects on milk fatty acid (FA) composition. Two enclosures laid out on an open grassland (OG) and a grazable forestland (GF) were exploited by 14 Camosciata goats. A commercial concentrate was supplemented during milking. Forty-five plots were randomly selected inside each enclosure and used to assess the species relative abundance (SRA) and phenological stage of plants, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…Furthermore, there are different results in the literature about ALA content in goat milk depending chemical parameters of ingested plants (lignine, crude protein, FAs, concentration of ALA on the pasture) (Park et al 2007;Iussig et al 2015). A higher ruminal bypass of dietary ALA has been suggested in goats compared to cow (Cornale et al 2014) and ALA was also found positively correlated with the type and relative abundance of dietary polyphenols (K€ alber et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are different results in the literature about ALA content in goat milk depending chemical parameters of ingested plants (lignine, crude protein, FAs, concentration of ALA on the pasture) (Park et al 2007;Iussig et al 2015). A higher ruminal bypass of dietary ALA has been suggested in goats compared to cow (Cornale et al 2014) and ALA was also found positively correlated with the type and relative abundance of dietary polyphenols (K€ alber et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…number of occurrences per 50 points of vegetation measurements). An SC value of 0.5% was attributed to all occasional species (those not recorded along the transect but within the vegetation plot) (Iussig et al 2015b). …”
Section: Vegetation and Plant Species Selection Surveysmentioning
confidence: 99%
“…A more complete understanding of nutritional regulation of milk secretion would contribute to the feeding and management practices development for altering milk composition and optimizing milk production [8,22]. Thus, one of the main objectives of this study was to determine effects of survey of relationship between pre-pubertal planes of nutrition with milk quality in Kurdish female kids in the west of Iran.…”
Section: Milkmentioning
confidence: 99%
“…Most livestock milk produced in the world is processed into cheese, yogurt and other dairy products. For this reason, the relationship between ewe nutrition and milk quality is mainly evaluated in terms of its technological and coagulation properties [7,8]. From lactation studies, the indirect evidence in ewe lambs proposes that before and after the main allometric growth phase, continuous rapid growth may depress mammary development as compared to feeding regimes including minimum one phase of limited feed intake [3,9,10].…”
Section: Introductionmentioning
confidence: 99%